Aza-BODIPY dyes with heterocyclic substituents and their derivatives bearing a cyanide co-ligand: NIR donor materials for vacuum-processed solar cells. Issue 21 (17th May 2017) - Li, Tian-yi; Meyer, Toni; Meerheim, Rico; Höppner, Marco; Körner, Christian; Vandewal, Koen; Zeika, Olaf; Leo, Karl
Abstract : Aza-BODIPY dyes with heterocyclic substituents and their derivatives with an asymmetric BF(CN) moiety were synthesized via a modified route using organolithium reagents. As strong NIR absorbers, the vacuum processed BHJ solar cell with an aza-BODIPY donor and a C60 acceptor achieved a PCE of 3%. Abstract : The need for NIR absorbing materials has become a focus of organic photovoltaics. We synthesize three benzannulated aza-BODIPY dyes with heterocyclic substituents, namely N -methyl pyrrole, N -methyl indole and 2-trimethylsilyl thiophene. With one fluorine atom in the BF2 moiety replaced by a cyano group, three corresponding derivatives are further synthesized. As NIR absorbers, these dyes present high molar extinction coefficients (65 100–104 500 L mol −1 cm −1 ) in solutions with absorption maxima in the range between 762 and 797 nm. In vacuum-deposited thin films, their absorption bands are further bathochromically shifted peaking from 830 to 849 nm and broadened. CV measurements and theoretical calculations demonstrate that the frontier molecular orbital levels of these compounds are suitable as donor materials in solar cells when combined with C60 as the acceptor. We obtain a PCE of 3.0% and a V oc of 0.61 V, which are rather high values for NIR absorbing vacuum processable small molecular donor compounds, with an absorption onset around 950 nm.